2019
DOI: 10.1007/s00726-019-02770-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-isocyanate urethane linkage formation using l-lysine residues as amine sources

Abstract: Non-isocyanate urethane linkage formation using L-lysine residues as amine sources, Amino Acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…An interesting renewable source for making the cyclic carbonates is diglycerol. Diglycerol dicarbonate (DGC), explored extensively in the literature for different PHU formulations, is derived from glycerol, which is a byproduct obtained from the hydrolysis of biomass wastes, the methanolysis of triglycerides, and the production of biodiesel . The worldwide annual production of glycerol has drastically increased in the past decade, and predictions showed that the production of glycerol was 6 times higher than the demand in 2020, making it an abundant raw material for the synthesis of PHUs. , Furthermore, DGC has a melting point of around 65 °C, , so bulk polyadditions are possible at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting renewable source for making the cyclic carbonates is diglycerol. Diglycerol dicarbonate (DGC), explored extensively in the literature for different PHU formulations, is derived from glycerol, which is a byproduct obtained from the hydrolysis of biomass wastes, the methanolysis of triglycerides, and the production of biodiesel . The worldwide annual production of glycerol has drastically increased in the past decade, and predictions showed that the production of glycerol was 6 times higher than the demand in 2020, making it an abundant raw material for the synthesis of PHUs. , Furthermore, DGC has a melting point of around 65 °C, , so bulk polyadditions are possible at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Its worldwide annual production has increased over 200% between the years 2000 and 2010, and it was predicted that by the year 2020, its production would be 6 times more than the demand, , which makes it an abundant raw material for the preparation of new sustainable HPHU sealants and adhesives. Many studies have characterized diglycerol dicarbonate (DGC)-based PHUs prepared from diamines of different chain lengths. As for the diamines, bio-based and petrochemical ones are available, and this work uses both with more attention given to poly­(dimethylsiloxane) diamines expected to give PHUs with high value-added end properties …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, elastin-like protein (ELP) and lactoglobulin (BLG) formed from whey protein as model proteins were reacted with BCC as described in Scheme 52. [157] There were four renewable and reprocessable PHU networks with crosslink density generated from two biobased polyfunctional carbonates, CSBO and SEC by Sumeng Hu and co-workers. DMA data reveal that CSBO-based PHU networks manifested multiple melt-state recycling steps under mild ChemistrySelect condition (110 °C, 30-40 min), as complete recovery of characteristics with crosslink density comparable to the first moulded samples.…”
Section: Synthetic Route To Obtain Nipu Under Catalytic Pathwaymentioning
confidence: 99%
“…have involved in generation of urethane linkages using lysine moiety to form five‐membered biscyclic carbonate (BCC) and reacted with protected lysine tripeptide, and heptapeptide. Indeed, elastin‐like protein (ELP) and lactoglobulin (BLG) formed from whey protein as model proteins were reacted with BCC as described in Scheme 52 [157] …”
Section: Synthetic Route To Obtain Nipu Under Catalytic Pathwaymentioning
confidence: 99%